A medieval miscellany - Labarge, Margaret Wade (Carleton University Press, 1997)
"This collection of occasional writings by renowned medieval scholar Margaret Wade Labarge considers an eclectic mix of themes and issues in the history of the Middle Ages. The varied lives of medieval women, their power and status within society, are depicted through their own writings; questions of medieval culture are linked to those facing humanity in our time; travel, as experienced by the most prestigious ambassador and by the lowliest pilgrim, is explored; and the origins and conditions of health care are examined. These themes have inspired or informed her eight major works, but are revisited here with the clarity, wit and discipline of a great teacher. These essays will give readers already acquainted with Labarge's work new pleasure, and provide an enticing path into medieval lives and time for new readers."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved